Letter from Carl D. Duncan to Patricia Whiting, March 15, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan mentions that he is going to Menlo Park and asks Whiting if there is anything she wants him to bring back for her. He promises strawberries.